2020
DOI: 10.15171/hpp.2020.06
|View full text |Cite
|
Sign up to set email alerts
|

Essential healthcare services provided to conflict-affected internallydisplaced populations in low and middle-income countries: A systematicreview

Abstract: Background: Conflict and violent crises have resulted in over 40 million of internally displaced persons (IDPs). Most affected regions lack access to basic health resources and generally rely on humanitarian support. The objective of this review was to appraise primary health service interventions among conflict-induced internally displaced populations in low and middle income countries between 2000 and 2019. Methods: A systematic review of literature in the following databases: Embase, MEDLINE, PsyArticles, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 63 publications
1
28
0
Order By: Relevance
“…Similarly to other studies in which the education was found a contributing factor while the other gender and marital status were insignificant. 22 The nature of residency has shown a significant effect on adherence and the patients from the IDPs living in the camps have shown non-adherence to the medication higher than patients living in village or cities. This finding is in consistence with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to other studies in which the education was found a contributing factor while the other gender and marital status were insignificant. 22 The nature of residency has shown a significant effect on adherence and the patients from the IDPs living in the camps have shown non-adherence to the medication higher than patients living in village or cities. This finding is in consistence with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…For example, training IDPs as health workers in camps has sometimes proven effective ( Ehiri et al., 2014 ). Using existing structures can amplify intervention success and reduce costs ( Ekezie et al., 2020 ). Regardless of the intervention type and duration, essential healthcare service interventions appear beneficial for IDP health, with programmes integrating multiple public healthcare components offering the greatest benefit, uptake and coverage ( Ekezie et al., 2020 ).…”
Section: Review Findingsmentioning
confidence: 99%
“…Using existing structures can amplify intervention success and reduce costs ( Ekezie et al., 2020 ). Regardless of the intervention type and duration, essential healthcare service interventions appear beneficial for IDP health, with programmes integrating multiple public healthcare components offering the greatest benefit, uptake and coverage ( Ekezie et al., 2020 ). Mobile service provision may also be beneficial in active-conflict areas ( Mullany et al., 2008 ), although the evidence remains weak ( McGowan et al., 2020 ).…”
Section: Review Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cases among internally displaced people (IDP) may easily be missed owing to limited access to health facilities for self-reporting [ 11 , 12 ]. Because of the ongoing armed conflict and natural disasters in Yemen, around 172,386 IDPs were present in different governorates in the country from January to December 2020 [ 13 ].…”
Section: Introductionmentioning
confidence: 99%